Pengaruh Budaya Organisasi Dan Gaya Kepemimpinan Terhadap Kepuasan Kerja Dan Dampaknya Terhadap Kinerja Pegawai Pada PT. Haleyora Power Rayon Cilegon - Fatari B. Sadeli (Universitas Mercu Buana, 2019)
This study aims to determine the Effect of Organizational Culture and Leadership Style on Employee Job Satisfaction and Its Impact on Employee Performance at PT. Haleyora Power Rayon Cilegon. The research method used in this study is a quantitative method by means of a survey with a causal approach. The results of the survey using the causal approach will be analyzed using the regression analysis approach. The analysis is used to facilitate the influence or causal of exogenous variables on endogenous. The results and discussion of this study are: First, The Effect of Organizational Culture on Employee Performance with a determination value of ry1 = (0.372) 2 = 0.139 or 13.9%. Second, the influence of Organizational Culture on Job Satisfaction with the value of determination rz1 = (0.469) 2 = 0.220 or 22.0%. Third, the influence of leadership style on employee performance with the value of determination ry2 = (0.336) 2 = 0.113 or 11.3%. Fourth, the influence of leadership style on job satisfaction with the determination value rZ2 = (0.427) 2 = 0.182 or 18.2%. Fifth, The Effect of Job Satisfaction on Employee Performance with a determination value ray = (0598) 2 = 0.358 or 35.8%. Sixth, Simultaneously the Effect of Organizational Culture, Leadership Style and Job Satisfaction, on Employee Performance with the determination value ry12z = (0.611) 2 = 0.373%. From the results of the discussion, it can be concluded that there is a significant influence on Organizational Culture and Leadership Styles on Employee Job Satisfaction and Its Impact on Employee Performance at PT. Haleyora Power Rayon Cilegon, Partially and Simultaneously.